SPOR TURİZMİ HİZMET KALİTESİ ÖLÇEĞİ GEÇERLİK VE GÜVENİRLİK ÇALIŞMASI - Osmanoğlu, Hasan; Üzüm, Hanifi; Karlı, Ünal; Aycan, Ali (Ekonomik ve Sosyal Araştırmalar Dergisi, 2018)
The purpose of this study was to develop a valid and reliable scale to measure the quality of the service provided to the athletes by hotels engaged in sport tourism. The scale named as “Sport Tourism Service Quality Scale” (STSQS). In the analysis process both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted. The analysis results revealed that the scale consisted of 28 items grouped under 5 sub-dimensions. The sub-dimensions of the scale was named as “Sport facilities, α=0.96”, “Staff, α=0.82”, “Entertainment, α=0.90”, “Hygiene, α=0.85” and “Room quality, α=0.80”. This five subdimensions explained the 72.32% of the variance. As a conclusion, “Sport Tourism Service Quality Scale” emerged as a valid and reliable scale in measuring the hotels’ service quality perceived by athletes.
Keywords: Kalite; Hizmet; Spor; Turizm; Otel